2019
DOI: 10.1097/pcc.0000000000001960
|View full text |Cite
|
Sign up to set email alerts
|

The Inadequate Oxygen Delivery Index and Low Cardiac Output Syndrome Score As Predictors of Adverse Events Associated With Low Cardiac Output Syndrome Early After Cardiac Bypass*

Abstract: supporting Libby Rogers. The remaining authors have disclosed that they do not have any potential conflicts of interest.derive scores for the first 12 hours after surgery. The IDO2 Index was calculated by Etiometry using vital signs and laboratory data. A modified LCOSS (mLCOSS) was calculated from clinical and therapeutic markers. The mean IDO2 and mLCOSS were compared within each matched pair using the Wilcoxon signed-rank test. IDO2 correctly differentiated adverse events in 13/28 matched pairs, with no evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…In contrast to platforms like Bedmaster™ and Etiometry® (the latter of which provides, e.g., a validated early-warning tool for shock 16 ), none of the aforementioned prognostic scores for mortality in critically ill children provides real-time analytics using continuously acquired physiologic monitoring data (e.g., minute-to-minute or higher frequency vital sign measures and/or waveforms). Neither Bedmaster™ nor Etiometry® offers a validated early-warning tool for impending cardiac arrest.…”
mentioning
confidence: 99%
“…In contrast to platforms like Bedmaster™ and Etiometry® (the latter of which provides, e.g., a validated early-warning tool for shock 16 ), none of the aforementioned prognostic scores for mortality in critically ill children provides real-time analytics using continuously acquired physiologic monitoring data (e.g., minute-to-minute or higher frequency vital sign measures and/or waveforms). Neither Bedmaster™ nor Etiometry® offers a validated early-warning tool for impending cardiac arrest.…”
mentioning
confidence: 99%
“…At present, domestic and foreign studies on the risk factors of LCOS after CHD in children are inconsistent. It is believed that the occurrence of LCOS is caused by multiple factors, including impaired systolic and diastolic function of the heart, changes in cardiac load, and activation of inflammatory transmitters [ 14 , 15 ]. The results of our study have found that age ≤ 4y, preoperative oxygen saturation ≤ 93%, two-way ventricular shunt, duration of CPB ≥ 60 min, postoperative residual shunt were the independent risk factors of LCOS in patients with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…A LCOS score (tachycardia, oliguria, toe temperature < 30 °C, volume administration > 30 mL/kg/day, decreased near infrared spectroscopy measurements, hyperlactatemia, and need for vasoactive/inotropes in excess of milrinone at 0.5 µg/kg/min) showed an AUC for a composite morbidity (prolonged mechanical ventilation, new infection, cardiopulmonary arrest, neurologic event, renal dysfunction, necrotizing enterocolitis, and extracorporeal life support) of 0.83 in 55 patients undergoing pediatric open heart surgery [ 11 ] . Later, a modified LCOS score was superior to the inadequate oxygen delivery index in predicting adverse events linked to LCOS in 536 bypass pediatric operations for congenital heart defects [ 12 ] .…”
Section: Discussionmentioning
confidence: 99%